2011
DOI: 10.4103/0255-0857.81798
|View full text |Cite
|
Sign up to set email alerts
|

Biotypes and virulence factors of Gardnerella vaginalis isolated from cases of bacterial vaginosis

Abstract: The present study was conducted to correlate the biotypes of Gardnerella vaginalis strains isolated from cases of bacterial vaginosis and their virulence factors. Thirty-two strains of G. vaginalis isolated from cases of bacterial vaginosis were biotyped. Adherence to vaginal epithelial cells, biofi lm production, surface hydrophobicity, phospholipase C and protease activity were tested on these isolates. Biotype 1 was the most prevalent (8; 25%), followed by biotype 2 (7; 21.9%) and biotypes 5 and 8 (5; 15.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…G. vaginalis also produces haemolysin, liberating nutrients for the feeding of other anaerobic bacteria. It has been suggested that U. urealyticum is the most virulent of the mollicutes [115], expressing haemolytic activity and secretion of enzymes such as elastase, IgA protease (reducing mucosal immunity), phospholipase C, [126], and urease which hydrolyses urea to cytotoxic ammonia. Vaginal sloughing is facilitated by the production of sialidase, prolidase [117,121] and putrescine by G. vaginalis , Mobilincus [122] Megasphaera , [62], Bactroides fragilis [122] and Prevotella bivia [82,117].…”
Section: Resultsmentioning
confidence: 99%
“…G. vaginalis also produces haemolysin, liberating nutrients for the feeding of other anaerobic bacteria. It has been suggested that U. urealyticum is the most virulent of the mollicutes [115], expressing haemolytic activity and secretion of enzymes such as elastase, IgA protease (reducing mucosal immunity), phospholipase C, [126], and urease which hydrolyses urea to cytotoxic ammonia. Vaginal sloughing is facilitated by the production of sialidase, prolidase [117,121] and putrescine by G. vaginalis , Mobilincus [122] Megasphaera , [62], Bactroides fragilis [122] and Prevotella bivia [82,117].…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous authors attempted to correlate differences between healthy and BV vaginal samples [54-57], no consensus was achieved, except that biofilm formation of G. vaginalis and a decrease in lactobacilli number could be considered as the initial stages in the pathogenesis of BV [10,58]. Swidsinski and colleagues already conducted an international follow-up study in which vaginal samples from several BV patients were analyzed by DNA-based FISH and a dense as well as active bacterial biofilm on vaginal mucosa was detected, primarily consisting of G. vaginalis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic diversity within the G. vaginalis species has also been shown in relation to virulence factors, such as production of sialidase and vaginolysin, initial adhesion, cytotoxic effect, biofilm formation, susceptibility to antimicrobials, and the ability of G. vaginalis to displace lactobacilli adhered to HeLa cells [18–22]. Association of G. vaginalis biotypes with BV has been evaluated in a number of studies, but the results have been contradictory [11, 19, 20, 2325]. Sialidase is utilized by some BV-associated bacteria, including G. vaginalis , for degradation and depletion of protective host mucus barriers [26, 27].…”
Section: Introductionmentioning
confidence: 99%